THE USE OF TUMOR NECROSIS FACTOR α INHIBITORS IN PATIENTS WITH WEBER-CHRISTIAN DISEASE - Olga Nikolayevna Egorova; B S Belov; S G RadenskaLopovok; O V Pushkova; N M Savushkina; Ya B Khrennikov; E L Nasonov (Научно-практическая ревматология, 2014)
Weber-Christian disease (WCD), also known as idiopathic lobular panniculitis, is a rare disease belonging to the group of diffuse connective tissue diseases. No therapy for WCD has been developed; empirical treatment is typically used. The first description of the use of tumor necrosis factor α inhibitors in a female patient with infiltrative WCD is presented. The tactics of managing this patient category are analyzed.